ChemInform Abstract: Synthesis and Magnetic Properties of β‐KVOF3. Issue 27 (8th July 2014) - Donakowski, Martin D.; Lu, Hongcheng; Gautier, Romain; Saha, Rana; Sundaresan, A.; Poeppelmeier, Kenneth R.
Abstract β‐KVOF3 is prepared by in‐situ reduction under hydrothermal conditions using a mixture of V2O5 and KBr (3:2) in aq.